2001
DOI: 10.1002/mde.1033
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in pre‐merger and post‐merger non‐bank financial institutions

Abstract: A two-part process is employed to analyse the role of efficiency in merger and acquisition (M&A) activity in Australian credit unions during the period 1993 to 1997. The measures of efficiency are derived using the nonparametric technique of data envelopment analysis. The first part uses panel data in the probit model to relate pure technical efficiency, along with other managerial, regulatory and financial factors, to the probability of merger activity, either as an acquiring or acquired entity. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 32 publications
5
26
0
3
Order By: Relevance
“…8 Fried et al (1999), Garden and Ralston (1999), and Ralston et al (2001). 9 Worthington (2001). 10 For a more extensive discussion of the application of efficiency testing methodologies see Worthington (2008).…”
Section: Credit Union Specific Control Variablesmentioning
confidence: 99%
“…8 Fried et al (1999), Garden and Ralston (1999), and Ralston et al (2001). 9 Worthington (2001). 10 For a more extensive discussion of the application of efficiency testing methodologies see Worthington (2008).…”
Section: Credit Union Specific Control Variablesmentioning
confidence: 99%
“…Similarly some other researchers (Favero & Pepi, 1995;Harris, Ozgen, & Ozcan, 2000;Worthington, 2001;Feroz, Kim, & Raab, 2005;Al-Sharkas et al, 2008;Odeck, 2008;Kwoka & Pollitt, 2010) found higher operating performances in the post merger periods, on the basis of data envelopment analysis (DEA) and stochastic frontier analysis (SFA). However, some studies observe mixed results.…”
Section: Operating Performance Approachmentioning
confidence: 75%
“…Some studies (Tarawaneh, 2006;Healy, Palepu, & Ruback, 1992;Lau, Proimos & Weight, 2008;Beena, 2004;Feroz, Kim & Raab, 2005;Harris, Ozen and Ozcan, 2000;Wen, 2002;Al-Sharkas et al, 2008;Odeck, 2008;Worthington, 2001;Kwoka & Pollitt, 2010) observed improvement in the operating performances in the post-merger period. However, other studies (Kumar, 2009;Yeh & Hoshino, 2002;Badreldin & Kalhoefer, 2009;Mantravadi & Reddy, 2008;Cabanda & Pascual, 2007;Pawaskar, 2001;Krishnasamy, Ridzwa & Vignesan, 2004;Rezitis, 2008;Sufian & Fadzlan, 2007) indicate decline or no change in the post-merger performances.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Pulley and Braunstein (1992) create a composite cost function whose purpose is to examine scope economies and other properties of multi-product firms. Worthington (2001) analyzes the role of efficiency in merger decisions of non-bank financial institutions using Austrian credit unions and finds, ex post, that loan portfolio diversification, management ability, earnings and asset size influence the probability of acquisition. Worthington adds that after the merger, the credit unions' pure technical efficiency and scale efficiency improve.…”
Section: Literature Review Of Vertical Bank Acquisitions Scale and Smentioning
confidence: 99%